A STUDY EXPLORING THE IMPLEMENTATION OF AI DRIVEN GAMIFICATION IN UG & PG EDUCATIONAL SETTINGS - MS. JANSHI RENGASWAMY, MS. ANITHA RENGASWAMY, DR. RAMRAJ NADAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study explores the implementation of AI-driven gamification tools in undergraduate (UG) and postgraduate (PG) educational environments. Data was collected through a field survey of 93 educators, aiming to investigate the frequency of AI tool usage, the primary purposes for their use, and the challenges educators face, particularly in terms of infrastructure and resource availability. The study utilized Jamovi for descriptive analysis and conducted a Chi-Square test to test the hypotheses. The results reveal that a significant proportion of educators (73.12%) use AI-driven gamification tools occasionally, with Kahoot! being the most widely used platform. However, challenges related to institutional infrastructure and resource availability remain prevalent, with 61% of educators reporting infrastructure-related difficulties and 77% indicating resource constraints. The research further examines the relationship between institutional infrastructure, administrative support, and educator confidence. The findings highlight the need for improved institutional support to ensure the effective use of AI-driven gamification tools and enhance the overall teaching experience.